Nanostructured Ta-Si-N diffusion barriers for Cu metallization - Kim, DJ; Kim, YT; Park, JW (AMER INST PHYSICS, 1997)
Diffusion barrier properties of nanostructured amorphous Ta-Si-N thin films with different N concentrations have been investigated in metallurgical aspects of Cu metallization. When the N content exceeds 40 at. %, the Ta-Si-N film remains in the nanostructure phase even after annealing at 1100 degrees C for 1 h and effectively prevents Cu diffusion after annealing at 900 degrees C for 30 min. The reason for the excellent thermal stability is that excess N atoms disturb the grain growth of TaSi2 phase and keep the Ta-Si-N film in the nanostructure phase during the high temperature annealing. The Ta-Si-N film with N content less than 40 at. % fails to prevent the Cu diffusion after annealing at 700 degrees C for 30 min. (C) 1997 American Institute of Physics.
Keywords: DEPOSITED TUNGSTEN